2014
DOI: 10.1111/apm.12284
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A10 expression correlates with serrated pathway features in colorectal carcinoma with microsatellite instability

Abstract: Annexin A10 (ANXA10) has recently been identified as a marker of sessile serrated adenomas/polyps of the colorectum. Although the serrated neoplasia pathway is thought to be involved in the majority of microsatellite instability-high (MSI-H) sporadic colorectal carcinomas (CRCs), the clinicopathological implications of ANXA10 expression in CRC are unknown. Here, we evaluated ANXA10 expression status in 168 MSI-H CRCs by immunohistochemistry. Among 168 MSI-H CRCs, nuclear staining for ANXA10 in tumor cells reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…ANXA10 has recently been identified as a marker of sessile serrated adenomas/polyps of the colorectum. By immunohistochemistry analysis of ANXA10 expression status in 168 MSI CRCs, Kim et al [54] found 17% of tumors exhibited positive ANXA10. Most of them were located in the right colon (96%; P < 0.001), as well as being significantly associated with CIMP phenotype (P < 0.001).…”
Section: Other Genesmentioning
confidence: 99%
“…ANXA10 has recently been identified as a marker of sessile serrated adenomas/polyps of the colorectum. By immunohistochemistry analysis of ANXA10 expression status in 168 MSI CRCs, Kim et al [54] found 17% of tumors exhibited positive ANXA10. Most of them were located in the right colon (96%; P < 0.001), as well as being significantly associated with CIMP phenotype (P < 0.001).…”
Section: Other Genesmentioning
confidence: 99%
“…50 Although extensive exonal microsatellite alterations and increased point mutations caused by mismatch repair defects bestow very considerable overlap on the altered gene expression signatures between the 2 MSI-H subtypes, the serrated neoplasia pathway-associated gene signature can be found in the CIMP-H/MSI-H subtype. 51 Because serrated polyps, including hyperplastic polyps, sessile serrated adenomas, and traditional serrated adenomas, are associated with aberrant gastric-type differentiation, the (58) ,.001…”
Section: Molecular Subtypes Based On Combined Cimpmentioning
confidence: 99%
“…and loss of intestinal expression (CDX2 and KRT20 loss). 51,52 Furthermore, histologic features that differ between the 2 MSI-H subtypes include sheeting appearance, eosinophilic cytoplasm, acinar appearance, signet ring cell formation, and stratified nuclei. The first 4 of these features are more frequent in the CIMP-H/MSI-H subtype, whereas the last feature is more frequent in the CIMP-0,L/MSI-H subtype.…”
Section: Cimp-h/msi-h Subtype Is Characterized By a Gain Of Gastric Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that expression of annexin A10 is a reliable marker of SSAs and the serrated pathway of CRC,16 17 46–51 and loss of Hes-1 expression can reliably differentiate SSAs from HPs 52. Nourbakhsh and Minoo sought to interrogate the concept that at least some TSAs may arise in association with precursor HP or SSA lesions, particularly those that develop in the right colon, by applying these two stains to a series of polyps from the right side of the colon with mixed features of TSA and SSA (as defined by Rex et al ) 7 16.…”
Section: Introductionmentioning
confidence: 99%